Pengaruh Flashcard terhadap Kemampuan Penguasaan Kosakata Bahasa Indonesia Pada Siswa MI Sunan Giri Pulo - Fitria Septiana Rohmana; Ali Mahsun (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Based on the results of pre-research on class II students of MI Sunan Giri Pulo Lor Jombang related to the ability to master Indonesian vocabulary is still low or still insufficient to support the learning series. In addition, the use of learning media has not been tried by teachers as a supporting tool for teaching and learning activities so that students easily feel bored and less interested. From these problems in learning Indonesian, appropriate media is needed to support teaching and learning activities. The type of quantitative experimental research uses the Wilcoxon test. This study was conducted with the intention of seeing the influence given by flashcards on the ability of class II students of MI Sunan Giri Pulo Lor Jombang in mastering Indonesian vocabulary. Data collection was carried out through observation, written tests such as pretest-posttest and documentation. Class II students of MI Sunan Giri Pulo Lor were determined as research subjects with a total of 13 students. The resulting research shows that the application of flashcard media is going well. There is progress in the ability of class II students in mastering Indonesian vocabulary with the mean rank results obtained between the pretest being 7.00 and the mean rank from the posttest results being 91.00. The results of the hypothesis test using the Wilcoxon test are known to obtain significance Asmyp Sig. (2-tailed) at 0.001 < 0.05. From these results, acceptance is carried out on Ha and rejection on H0, which means that flash card media has an influence on the ability of class 2 students of MI Sunan Giri Pulo Lor Jombang in mastering Indonesian vocabulary.